Streptococcus suis DivIVA Protein Is a Substrate of Ser/Thr Kinase STK and Involved in Cell Division Regulation - Ni, Hua; Fan, Weiwei; Li, Chaolong; Wu, Qianqian; Hou, Hongfen; Hu, Dan; Zheng, Feng; Zhu, Xuhui; Wang, Changjun; Cao, Xiangrong; Shao, Zhu-Qing; Pan, Xiuzhen (Frontiers in Cellular and Infection Microbiology, 2018)
Streptococcus suis serotype 2 is an important swine pathogen and an emerging zoonotic agent that causes severe infections. Recent studies have reported a eukaryotic-like Ser/Thr protein kinase (STK) gene and characterized its role in the growth and virulence of different S. suis 2 strains. In the present study, phosphoproteomic analysis was adopted to identify substrates of the STK protein. Seven proteins that were annotated to participate in different cell processes were identified as potential substrates, which suggests the pleiotropic effects of stk on S. suis 2 by targeting multiple pathways. Among them, a protein characterized as cell division initiation protein (DivIVA) was further investigated. In vitro analysis demonstrated that the recombinant STK protein directly phosphorylates threonine at amino acid position 199 (Thr-199) of DivIVA. This effect could be completely abolished by the T199A mutation. To determine the specific role of DivIVA in growth and division, a divIVA mutant was constructed. The ΔdivIVA strain exhibited impaired growth and division, including lower viability, enlarged cell mass, asymmetrical division caused by aberrant septum, and extremely weak pathogenicity in a mouse infection model. Collectively, our results reveal that STK regulates the cell growth and virulence of S. suis 2 by targeting substrates that are involved in different biological pathways. The inactivation of DivIVA leads to severe defects in cell division and strongly attenuates pathogenicity, thereby indicating its potential as a molecular drug target against S. suis.